Nasionalisme dalam Pembelajaran Sejarah: Strategi Pedagogis dan Tantangan Implementasi di Era Global (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to analyze the role of history learning in fostering nationalism and identify pedagogical strategies and the challenges of their implementation in the era of globalization. The study employed a qualitative approach with library research methods, which examined various scientific literature related to nationalism in history learning. Data were collected from scientific journal articles, then analyzed using content analysis techniques to identify key themes and patterns. The results indicate that history learning plays a crucial role in building historical awareness and national identity through the integration of national values ​​into learning materials. Pedagogical strategies that are contextual, participatory, and reflective have proven more effective in instilling nationalism than rote memorization approaches. However, their implementation faces challenges such as the influence of globalization, low interest in learning history, and limited learning innovation. This study emphasizes the importance of developing innovative history learning strategies to strengthen the nationalism of the younger generation in the global era